The development of functional drinks made from telang flower (Clitoria ternatea) with lime juice addition - Endah Puspitojati; Novia Aristi Rahayu; Nur Fatimah; Sumarna Sumarna (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Telang (Clitoria ternatea) is a medicinal flower used in food and beverages. The beverages made from this flower are commonly available in Indonesia, but their properties have not been extensively investigated. Thus, this study aimed to determine the physicochemical properties of telang flower beverages, such as pH, vitamin C, anthocyanin, and hedonic level. The study employed a complete randomized factorial design. The weight of dried flowers and volume of lime juice were used as independent variables. The De Garmo effectiveness index selected the four best physicochemical characteristics of beverages. The addition of dried flower and lime juice resulted in a significant difference in anthocyanin, vitamin C, pH, and free radical inhibition activity. Four treatment beverages with good chemical qualities were chosen to be examined hedonically. The treatment with lime juice addition resulted in a significant difference in the hedonic level of color, sweetness, and acidity (p0.05). There was, however, no significant difference in the aroma produced in the beverages (p0.05). The best formulation of the telang flower beverage was based on hedonic analysis with a combination of 4.5 g of telang flower and 5 ml of lime juice, resulting in a beverage with less sugar and fewer calories.